Distribution and content of calcium and potassium in eucalyptus leaves infected with Calonectria pteridis. Issue 9 (8th August 2020) - Soares, Thaissa de Paula Farias; Ferreira, Maria Alves; Pozza, Adélia Aziz Alexandre; Pozza, Edson Ampélio; Mafia, Reginaldo Gonçalves
Abstract: Calonectria leaf spot, caused by Calonectria pteridis, is a serious problem in Eucalyptus crops in both nursery and the field. Under ideal conditions, the disease can cause severe defoliation. It is known that calcium and potassium are directly related to the plant's resistance to pathogens. Thus, the knowledge of how a balanced fertilization of Ca and K interferes in the distribution of these nutrients at the infection site would contribute to elucidate the resistance of the plant related to its nutrition. This study investigated the effect of calcium and potassium fertilizer application on the content and distribution of these nutrients in the symptomatic leaf area, transition zone and asymptomatic leaf area over time. Eucalyptus seedlings were grown in nutrient solution under different Ca and K treatments (6 mmol/L K + 4 mmol/L Ca, 6 mmol/L K + 8 mmol/L Ca and 9 mmol/L K + 12 mmol/L Ca) and inoculated with C. pteridis . Leaves were removed at 24, 48 and 72 hr after inoculation (hai) and evaluated by X‐ray microanalysis. The highest calcium content among the different leaf areas was observed in the symptomatic area, and the levels in this area increased over time, with the highest mean value observed at 72 hai in the 6K + 8Ca treatment. In the other treatments, the mean calcium content peaked at 48 hai and then decreased. A similar pattern in asymptomatic tissue was observed for potassium in the 6K + 8Ca treatment. Fertilization with calcium and potassium directly affected the demand and availability of nutrients at different times during infection. These results demonstrate that plant defence responses and their continuity over time during infection rely on balanced calcium and potassium fertilization because these nutrients are directly involved in plant resistance to the pathogen.